La observación de situaciones cotidianas, estrategia didáctica para desarrollar competencias científicas (2017)
The development of scientific competences is one of the great challenges that teachers must face, so this research intends to associate tasks, observations, understanding everyday events and the development of scientific competences. Comparing and analyzing the results obtained; It is found that the strategy favorably influences the development of scientific competences. Therefore, it is concluded that the main elements that can mediate this process are oriented towards situations that show students their own contexts, experiences, cases and anecdotes, generating cognitive conflicts and thus be able to look for the proposed objectives, assuming sequences to solve problems. These steps or stages can be achieved under schemes of pedagogical acts that contain a sequence of teaching and learning (SEA), which according to Caamaño (2011) is the planning of the process to teach and learn. The findings are based on the theory of Cognitive Mediation, proposed by Feuerstein, 1988, 1991; giving relevance to previous experiences (the observation of everyday situations) in their new one, which should be activated when combined with didactic strategies, typical of constructivist and activist approaches. (Castillo, 2008), De Zubiría (2006). And that for the development of teaching-learning processes, it is fundamental to incorporate the context in which the student develops from the field of everyday life, (López de Maturana, 2015)